Left Ventricular Remodeling Following Balloon Mitral Valvuloplasty in Rheumatic Mitral Stenosis: Magnetic Resonance Imaging Study - Samaan, Amir Anwar; Said, Karim; Aroussy, Wafaa El; Hassan, Mohammed; Romeih, Soha; El Sawy, Amr; Fawzy, Mohammed Eid; Yacoub, Magdi (Frontiers in Cardiovascular Medicine, 2021)
Background: Rheumatic heart disease affects primarily cardiac valves, it could involve the myocardium either primarily or secondary to heart valve affection. The influence of balloon mitral valvuloplasty (BMV) on left ventricular function has not been sufficiently studied. Aim: To determine the influence of balloon mitral valvuloplasty (BMV) on both global and regional left ventricular (LV) function. Methods: Thirty patients with isolated rheumatic mitral stenosis (MS) were studied. All patients had cardiac magnetic resonance imaging (CMR) before, 6 months and 1 year after successful BMV. LV volumes, ejection fraction (EF), regional and global LV deformation, and LV late gadolinium enhancement were evaluated. Results: At baseline, patients had median EF of 57 (range: 45–69) %, LVEDVI of 74 (44–111) ml/m2 and LVESVI of 31 (14–57) ml/m2 with absence of late gadolinium enhancement in all myocardial segments. Six months following BMV, there was a significant increase in LV peak systolic global longitudinal strain (GLS) (−16.4 vs. −13.8, p < 0.001) and global circumferential strain (GCS) (−17.8 vs. −15.6, p = 0.002). At 1 year, there was a trend towards decrease in LVESVI (29 ml/m2, p = 0.079) with a significant increase in LV EF (62%, p < 0.001). A further significant increase, compared to 6 months follow up studies, was noticed in GLS (−17.9 vs. −16.4, p = 0.008) and GCS (−19.4 vs. −17.8 p = 0.03). Conclusions: Successful BMV is associated with improvement in global and regional LV systolic strain which continues for up to 1 year after the procedure.